Reconstruction Of Provincial Authority In The Field Of Marine Affairs And Fisheries To Regency/City Governments In Realizing The Welfare Of Small-Scale Fishermen In Indonesia - Ahmad Duroni Nasution; Ramlan Ramlan; Ida Nadirah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Horizontal conflicts occurred after the UUPD came into effect because there were regulations regarding changes in marine zoning for small fishing communities. Meanwhile, the authority of the district/city government over coastal areas and small islands has been regulated in the UUPWP3K that the authority of the regional government to manage coastal and small island resources. This study aims to analyze the provisions of laws and regulations on regional government and coastal area management as regulated in the regulations on coastal areas and small islands, and how to reconstruct the authority of the provincial government to the district/city government as before. The research method used is normative legal research. Normative legal research is research that is carried out or directed at legislation, namely the relationship between one regulation and another and its relation to implementation in practice. The results of the study show that since the UUPD came into effect, the authority to manage the marine and fisheries sector as well as coastal areas and small islands by the district/city government has been reduced. The zoning area of 0-4 miles which was originally managed by the district/city government is now managed by the provincial government, thus making the provincial authority zoning 0-12 miles